2012
DOI: 10.1007/s00192-012-1747-6
|View full text |Cite
|
Sign up to set email alerts
|

Is cervical elongation associated with pelvic organ prolapse?

Abstract: Introduction and Hypothesis It is commonly believed that pelvic organ prolapse is associated with cervical elongation. However, cervical lengths have not been formally compared between women with prolapse and those with normal support. Methods Cervix and uterine corpus lengths were measured on magnetic resonance images in a case-control study of 51 women with prolapse and 46 women with normal support determined by pelvic organ prolapse (POP) quantification (POP-Q) examination. Group matching ensured similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 21 publications
1
34
0
1
Order By: Relevance
“…The literature contains no clear definition of cervical elongation. Some authors suggest a definition including the corpus uteri/cervix ratio (CCR) of < 1.5 [28, 29]. Using that definition, Mothes et al found that cervical elongation was present in 97.6 % of patients undergoing hysterectomy due to objective and symptomatic uterine POP stage II–IV, which would suggest that a considerable amount of the patients in the present study might have had some degree of cervical elongation [28].…”
Section: Discussionmentioning
confidence: 95%
“…The literature contains no clear definition of cervical elongation. Some authors suggest a definition including the corpus uteri/cervix ratio (CCR) of < 1.5 [28, 29]. Using that definition, Mothes et al found that cervical elongation was present in 97.6 % of patients undergoing hysterectomy due to objective and symptomatic uterine POP stage II–IV, which would suggest that a considerable amount of the patients in the present study might have had some degree of cervical elongation [28].…”
Section: Discussionmentioning
confidence: 95%
“…8 A previous study reported that cervical elongation is found in one-third of women with POP, with the extent of elongation increasing with greater degrees of uterine descent. 7 Another study comparing laparoscopic uterosacral plication in hysteropexy and hysterectomy groups, observed higher prevalence of postoperative cervical elongation in the former group. 28 In the present study, apical recurrence was observed more frequently among those with uterine preservation without trachelectomy.…”
Section: Discussionmentioning
confidence: 99%
“…4 The uterus itself is regarded as an important factor in pelvic floor stability and sexual health. 5 Some studies found no significant difference in the cure rates of POP whether or not the uterus was preserved, 6,7 but there was some concern over postoperative cervical elongation among those who had uterine preservation. 8 The present study evaluated long-term outcome of SSF in combination with various other compartment defect repairs using native tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have mainly focused on characterizing the extracellular matrix (ECM) of connective tissue that support the pelvic floor, such as the vaginal wall [2, 711], the uterosacral ligaments [12, 13], and the pubocervical fascia [13, 14]. Different outcomes have been reported, but the overall consensus is that the connective tissue of the vaginal wall is abnormal in women with POP [15].…”
Section: Introductionmentioning
confidence: 99%